Learner Errors In Writing Descriptive Text Made By Students Of Smp Al Islam Kartasura - Amalia, Dinar Rizqi (2016)
The study aims at describing the learners' error made by eighth grade students of SMP AL Islam Kartasura in their composition in writing descriptive text; identify the types of lexical error, syntactical errors, and discourse errors; explain the frequency of each type of errors; describe the dominant type of errors; and identify the sources of error. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation and documentation technique. The are some steps for collecting the data, they are: the writer asks the students to write descriptive text, the writer collects the data in the form erroneous sentences and paragraph, the writer identifies the composition and marks the types of error, and the last the writer lists the erroneous sentences and classifies them into the classification of errors. The collected data are analyzed by using Dulay, Burt and Krashen classification of errors theory, Slamet's theory for the frequency of each type of error, and Brown's theory for sources of error. The results of the research show that the eighth grade students of SMP AL Islam Kartasura make 291 errors in their composition. The writer finds that from 291 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are lexical errors that cover: misspelling 12,37% and literal translation (the use of Indonesian construction) 6,87%. Syntactical errors consist of omission of {-s} as plural marker 4,12%, omission of {-s} as third singular person marker 10,31%, misselection of have instead of has 8,25%, the use of verb-ing in structure phrase 1,72%, omission of verb 2,40%, omission of be 1,5%, addition of be 2,40%, the use of preposition in prepositional phrase 3,44%, omission of article 1,37%, addition of the article 1,72%, misordering in noun phrase 19,93%, misordering in phrase 1,37%, and the last is addition of unnecessary word 5,50%. Discourse errors 2,06% that cover component of discourse in reference 2,06%. The writer also finds 2 dominant sources of errors namely interlingual transfer and intralingual transfer